ESTIMASI PARAMETER UNTUK DISTRIBUSI HALF LOGISTIK - Rizqi Elmuna Hidayah; Nur Salam; Dewi Sri Susanti (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2013)
Point estimation is a value obtained from the samples and used as anestimator of the parameter whose value is unknown. To determine the point estimatorcan be used several methods, such as Maximum Likelihood Estimator (MLE) and Methodof Moments Estimator (MME). Half logistic distribution is used for lifetime data such asthe survival data of a unit or individual of a particular situation in terms of failure time.In this journal, several methods for estimating the location and scale parameters of thehalf-logistic distribution.